2021
DOI: 10.1186/s12935-021-01785-3
|View full text |Cite
|
Sign up to set email alerts
|

Pien Tze Huang (PZH) as a Multifunction Medicinal Agent in Traditional Chinese Medicine (TCM): a review on cellular, molecular and physiological mechanisms

Abstract: Relevance Pien Tze Huang (PZH) is a well-known Traditional Chinese Medicine (TCM), characterized by a multitude of pharmacological effects, such as hepatoprotection and inhibition of inflammation and cell proliferative conditions. Many of these effects have been validated at the cellular, molecular and physiological levels but, to date, most of these findings have not been comprehensively disclosed. Objectives This review aims to provide a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 92 publications
(137 reference statements)
0
10
0
Order By: Relevance
“…PZH is a traditional Chinese remedy that has been found to be effective in treating inflammatory diseases and cancer, more recent studies have investigated its pharmacological effects ( Chen, 2021 ). In our research, we observed for the first time that PZH facilitates wound healing in different biological diabetic models, promotes the expression of NRF2 and its downstream antioxidant genes HO-1 and SOD-1, increases the expression of VEGF-A, PDGF and EGF in diabetic wounds, and reduces the levels of TNF-α, IL-1β, and IL-6 in diabetic mouse serum, contributing to the repair of diabetic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…PZH is a traditional Chinese remedy that has been found to be effective in treating inflammatory diseases and cancer, more recent studies have investigated its pharmacological effects ( Chen, 2021 ). In our research, we observed for the first time that PZH facilitates wound healing in different biological diabetic models, promotes the expression of NRF2 and its downstream antioxidant genes HO-1 and SOD-1, increases the expression of VEGF-A, PDGF and EGF in diabetic wounds, and reduces the levels of TNF-α, IL-1β, and IL-6 in diabetic mouse serum, contributing to the repair of diabetic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PZH perhaps heals a wide range of liver injuries and inflammation (Fu et al, 2016;Qi et al, 2017;Li et al, 2018;Zhang et al, 2018). Owing to its history of around 500 years, PZH was listed as one of the Chinese National Protected TCM in the 1990s (Chen, 2021). Also, the major active components with their potential functions such as neuro-protecting effects, anti-cancer effects, and antiinflammatory effects including most of the pharmacological effects had been validated and reported (Yan et al, 2017; Frontiers in Pharmacology frontiersin.org et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in the treatment of dementia, cerebral ischemia, myocardial infarction, diabetic peripheral neuropathy, vertebral endplate degeneration, injury, inflammation, cancer, and other diseases (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Muscone is one of the anti-inflammatory constituents in a well-known traditional Chinese medicine named Pian-Tze Huang (39). It can reach various parts of the central nervous system through the blood-brain barrier within 5 minutes after gastric administration and within 2 minutes after caudal vein injection (40).…”
Section: Original Articlementioning
confidence: 99%